Low grade of satisfaction related to the use of current systemic therapies among pustular psoriasis patients: a therapeutic unmet need to be fulfilled - Coscarella, Giulia; Falco, Gennaro Marco; Palmisano, Gerardo; Ippoliti, Elena; De Luca, Eleonora; Gori, Niccolò; Di Nardo, Lucia; Caldarola, Giacomo; De Simone, Clara; Chiricozzi, Andrea; Peris, Ketty (Frontiers in Medicine, 2024)
Introduction Pustular psoriasis is considered a separate entity from plaque psoriasis and can be cathegorized as generalized pustular psoriasis (GPP), acrodermatitis continua of Hallopeau, or palmoplantar pustulosis (PPP). Current guidelines mostly include treatment options that have not been specifically developed for the treatment of pustular psoriasis. The majority of them does not have indication for the treatment of pustular psoriasis. Their effectiveness and safeness have been described in small cohort-based studies or case series with a low level of evidence. Previous studies evaluated treatment response through physician-based assessment but none reported patient satisfaction to treatment, quality of life and patient perception of disease severity during systemic therapies, particularly with biologics commonly used in plaque psoriasis. This study aimed to investigate patient satisfaction to treatment and patients’ quality of life during treatment, correlating patient-reported outcomes with residual disease severity. Methods A cross-sectional, cohort-based, single center study included patients affected by pustular psoriasis undergoing treatment with systemic agents. Demographic, clinical characteristics were collected. Treatment satisfaction as well as disease severity were assessed through dedicated assessment scores. Results A total of 31 patients affected by GPP or PPP were included. Despite biologic treatment, 80.6% of patients continued to experience mild-to-severe disease activity, with discrepancies between patient and physician assessments. Patients reported a substantial impairment in their quality of life, with notable limitations in physical activity and emotional distress. Mental health conditions, such as depression and anxiety disorders, were common. Treatment satisfaction varied, with moderate scores for effectiveness and convenience. Only a small proportion of patients (41.9%) reported complete or high overall treatment satisfaction. GPP and PPP subcohorts exhibited similar quality of life and treatment satisfaction levels. Discussion This study highlights the suboptimal control of PP despite biologic therapies, resulting in a significant impact on patients' quality of life and treatment satisfaction. The findings highlight the need for specific therapies and standardized guidelines for managing PP. New targeted therapies, such as spesolimab, hold promise for optimizing treatment satisfaction and improving patients' quality of life. Future research should focus on refining treatment strategies to address the unmet needs of PP patients comprehensively.